Cozywrap: to secure and protect patients in a comforting way / Farah Hidayah Mohd Fazli … [et al.] - Mohd Fazli, Farah Hidayah; Ahmad, Mas Suryalis; Yahaya, Norjehan; Zulkifly, Nur A’thirah; Ibrahim, Siti Hajar; Ismail, Mohd Isyrafuddin (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Special care dentistry encountered difficulty handling patients with behavioural issues while delivering daily dental treatment. These individuals may be restrained using a physical restrainer or a papoose board as one method of patient management. However, this method can be unpleasant to the patients because of the physical features of the papoose board. In addition, the majority of papoose boards are designed for children with behavioural issues and not for adults. Therefore, there are limitations in providing clinical holding for much taller and larger adult patients with particular demands. It is necessary to design a physical restrainer or papoose board for adult patients with special needs so that dental care can be delivered in a dental clinic. CozyWrap is a physical restrainer product that act as a wrap and a blanket for uncooperative patients. It is specifically designed to make the patient feel more comfortable and less stressed during dental treatment. In addition, CozyWrap can be used for anxious patients because the material and colour chosen for this product will help anxious patients feel more comfortable during dental treatment. CozyWrap will help delivering dental care for special needs patients it much more fun and relaxed condition thus helping to desensitize the patient with dental environment.